2017
DOI: 10.5897/ajar2016.11860
|View full text |Cite
|
Sign up to set email alerts
|

Wheat blast research: Status and imperatives

Abstract: Wheat blast is relatively a new disease of wheat that first appeared in Brazil in 1985. It did spread to some other neighbouring countries in the following years and owing to its predisposing factors, was feared to be capable of moving across continental boundaries. The disease has now been reported from Bangladesh. Wheat blast at best can be described as poorly understood as both pathogen and its pathogenicity as well as host and its ability to resist need to be investigated before breeders could confidently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This is evident based on the increase in the yearly number of original articles and reviews published after the major epidemics reported in the Cerrado, Brazil, and disease's introduction into both Asia and Africa (Figure 2A). (Rajiv 2017;Sadat and Choi 2017;Cruz and Valent 2017;Mottaleb et al 2018Mottaleb et al , 2019Ceresini et al 2018Ceresini et al , 2019Islam et al , 2020Kamoun et al 2019;Tembo 2019;Yesmin et al 2020;Mbinda and Masaki 2021, Singh et al 2021, Tosa 2021. While some aspects have been given more attention, such as the taxonomy and population genetics (Couch and Kohn 2002;Tanaka et al 2009;Luo and Zhang 2013;Maciel et al 2014;Murata et al 2014;Klaubauf et al 2014;Gladieux et al 2015Gladieux et al , 2018Castroagudín et al 2016;Valent et al 2019), chemical control (Kim et al 2003;Cruz et al 2011Cruz et al , 2019Pagani et al 2014;Rocha et al 2014;Castroagudín et al 2015;Oliveira et al 2015;Dorigan et al 2019;D'Ávila et al 2021;Ascari et al 2021) and host genetic resistance (Cruz et al 2016b;Anh et al 2018;Rocha et al 2019;…”
Section: Economical and Scientific Importancementioning
confidence: 99%
“…This is evident based on the increase in the yearly number of original articles and reviews published after the major epidemics reported in the Cerrado, Brazil, and disease's introduction into both Asia and Africa (Figure 2A). (Rajiv 2017;Sadat and Choi 2017;Cruz and Valent 2017;Mottaleb et al 2018Mottaleb et al , 2019Ceresini et al 2018Ceresini et al , 2019Islam et al , 2020Kamoun et al 2019;Tembo 2019;Yesmin et al 2020;Mbinda and Masaki 2021, Singh et al 2021, Tosa 2021. While some aspects have been given more attention, such as the taxonomy and population genetics (Couch and Kohn 2002;Tanaka et al 2009;Luo and Zhang 2013;Maciel et al 2014;Murata et al 2014;Klaubauf et al 2014;Gladieux et al 2015Gladieux et al , 2018Castroagudín et al 2016;Valent et al 2019), chemical control (Kim et al 2003;Cruz et al 2011Cruz et al , 2019Pagani et al 2014;Rocha et al 2014;Castroagudín et al 2015;Oliveira et al 2015;Dorigan et al 2019;D'Ávila et al 2021;Ascari et al 2021) and host genetic resistance (Cruz et al 2016b;Anh et al 2018;Rocha et al 2019;…”
Section: Economical and Scientific Importancementioning
confidence: 99%
“…Adapted from [65]. began to develop short, medium, and long-term strategies to limit the spread of the disease as well as turn their attention to sustaining wheat production in this region to face the lethal disease [14,68,71]. Scientists and policymakers in the region took several initiatives in collaboration with CIMMYT, ACIAR, and the USA for the development of a wheat blast resistant wheat variety.…”
Section: Wheat Blast: a New Threat To Food Securitymentioning
confidence: 99%